Patients with post-COVID-19 condition show minor blood transcriptomic changes, with altered erythrocyte gene expression in a male subgroup - Karisola, Piia; Kanerva, Mari; Vuokko, Aki; Liira, Helena; Wang, Shuyuan; Kvarnström, Kirsi; Varonen, Mikko; Suojalehto, Hille; Alenius, Harri (Frontiers in Immunology, 2025)
BackgroundThe mechanisms underlying persistent symptoms after non-severe COVID-19 remain unclear. This study aimed to investigate transcriptomic changes in peripheral blood cells of patients with post-COVID-19 condition (PCC) and assess if distinct clinical subtypes with specific gene signatures could be identified.MethodsThe cohort included 111 PCC patients from the SARS-CoV-2 Omicron variant era, with 57 recovered (Recov) and 54 having prolonged symptoms indicative of PCC. The results were compared to 63 healthy controls (Ctrl) without known SARS-CoV-2 infection. Clinical data included patient assessments, laboratory results, comorbidities, and questionnaires on quality of life and functioning. Transcriptomic analysis and cellular deconvolution methods were used on total RNA from peripheral blood mononuclear cells (PBMCs).ResultsPCC patients had more comorbidities (mean 1.3) and more frequently (59%) at least one comorbidity than recovered patients (31%) and controls (24%). Overall, past COVID-19 illness or current PCC symptoms caused minimal changes in the blood cell transcriptome, with only 3–6 differentially expressed genes (DEGs) identified across comparisons. However, a subset of male PCC patients exhibited an increased fraction of deconvoluted erythroblasts and significant genome-wide gene expression changes, with 399 DEGs compared to recovered and control males. These genes were enriched in pathways related to heme metabolism and gas exchange in erythrocytes.ConclusionsPersistent symptoms in PCC are multifactorial and not directly linked to peripheral blood cell gene expression changes. However, a subgroup of male PCC patients shows distinct erythrocyte responses that may contribute to long-term symptoms.